How does preclinical laboratory training impact physical examination skills during the first clinical year? A retrospective analysis of routinely collected objective structured clinical examination scores among the first two matriculating classes of a reformed curriculum in one Polish medical school. Issue 8 (1st September 2017) - Świerszcz, Jolanta; Stalmach-Przygoda, Agata; Kuźma, Marcin; Jabłoński, Konrad; Cegielny, Tomasz; Skrzypek, Agnieszka; Wieczorek-Surdacka, Ewa; Kruszelnicka, Olga; Chmura, Kaja; Chyrchel, Bernadeta; Surdacki, Andrzej; Nowakowski, Michał
Abstract : Objective: As a result of a curriculum reform launched in 2012 at our institution, preclinical training was shortened to 2 years instead of the traditional 3 years, creating additional incentives to optimise teaching methods. In accordance with the new curriculum, a semester-long preclinical module of clinical skills (CS) laboratory training takes place in the second year of study, while an introductory clinical course (ie, brief introductory clerkships) is scheduled for the Fall semester of the third year. Objective structured clinical examinations (OSCEs) are carried out at the conclusion of both the preclinical module and the introductory clinical course. Our aim was to compare the scores at physical examination stations between the first and second matriculating classes of a newly reformed curriculum on preclinical second-year OSCEs and early clinical third-year OSCEs. Design: Analysis of routinely collected data. Setting: One Polish medical school. Participants: Complete OSCE records for 462 second-year students and 445 third-year students. Outcome measures: OSCE scores by matriculation year. Results: In comparison to the first class of the newly reformed curriculum, significantly higher (ie, better) OSCE scores were observed for those students who matriculated in 2013, a year after implementing the reformed curriculum. This finding was consistent for both second-year and third-year cohorts. Additionally, the magnitude of the improvement in median third-year OSCE scores was proportional to the corresponding advancement in preceding second-year preclinical OSCE scores for each of two different sets of physical examination tasks. In contrast, no significant difference was noted between the academic years in the ability to interpret laboratory data or ECG — tasks which had not been included in the second-year preclinical training. Conclusion: Our results suggest the importance of preclinical training in a CS laboratory to improve students' competence in physical examination at the completion of introductory clinical clerkships during the first clinical year.